2021
DOI: 10.1111/ans.16927
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood circumcision in Australia: Trends over 20 years and interrupted time series analysis

Abstract: Background Male circumcision is one of the most common surgical procedures performed in the Australian private sector. This study examines the trends in childhood circumcision throughout the early 21st century. Methods Circumcisions performed between 2000 and 2019 amongst preschool‐aged Australian boys (0–4 years) were obtained from the Medicare Benefits Schedule. Quarterly data for Victoria and South Australia were divided into three phases separated by (i) state‐wide bans of non‐therapeutic circumcision in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…This would include multiple cases for some individuals and none for others. In Australia, conversely, if there was an increase in the prevalence of NMC from the level of 19% in 2019 [132] to 90%, it has been calculated that this would result in approximately 77,000 fewer cases of adverse medical conditions over the lifetime of the 2019 annual male birth cohort of 157,000 [131]. #Based on data for circumcised vs. uncircumcised males [112,128,150,151].…”
Section: Consequences Of Nmc For Disease Prevalence In Anglophone Cou...mentioning
confidence: 99%
“…This would include multiple cases for some individuals and none for others. In Australia, conversely, if there was an increase in the prevalence of NMC from the level of 19% in 2019 [132] to 90%, it has been calculated that this would result in approximately 77,000 fewer cases of adverse medical conditions over the lifetime of the 2019 annual male birth cohort of 157,000 [131]. #Based on data for circumcised vs. uncircumcised males [112,128,150,151].…”
Section: Consequences Of Nmc For Disease Prevalence In Anglophone Cou...mentioning
confidence: 99%
“…A 2021 study of Medical Benefits Scheme (MBS) claims found that early MC in Australia declined from a peak of ~85% in the 1950s to 18.75% in 2019 [ 8 ]. The authors concluded that “Medical and surgical authorities may have played an important role in the gradual reduction of procedures over the last decade”.…”
Section: Trendsmentioning
confidence: 99%
“…In Australia and New Zealand, the lack of government coverage for non-therapeutic MC in public health systems would similarly be having cost impacts for treatment of medical conditions protected against by neonatal MC. An increase in early MC in Australia to 85% from the current level of 18.75% [ 8 ] would avoid 77,000 cases of infections and other adverse medical conditions over the lifetime for each annual birth cohort ( Table 1 ).…”
Section: Cost Benefitmentioning
confidence: 99%
See 2 more Smart Citations